The Effect of Integration of English Learning and Character Building based Artificial Intelligence (AI) on Student Learning Outcomes - Muh. Saiful Anwar; Zulfah Fakhruddin; Ambo Dalle (Institut Agama Islam Negeri Palopo, 2025)
Abstract This study aims to evaluate the effectiveness of integrating artificial intelligence (AI)-based English learning with students' character development, particularly in narrative text writing. AI tools such as Grammarly, QuillBot, and ProWritingAid are used to support this learning process. The research focuses on analyzing the impact of technology integration on students' academic achievement and character building of responsibility, creativity, and confidence. The study used an experimental design involving two groups, namely experimental and control. The experimental group received AI tools-based learning for six sessions, with each tool being used in turn to improve students' narrative texts. Data was collected through tests to evaluate students' writing skills, questionnaires to measure character development, and observation sheets to monitor students' interactions during learning. Data was analyzed using paired T-test and independent T-test techniques to compare the results between experimental and control groups. The results showed that the use of AI tools had a significant impact on students' character development, especially in the aspects of responsibility, creativity, and self-confidence, based on questionnaire and observation data. However, the impact on academic achievement was not significant within the limited duration of the study. This finding confirms that the integration of AI-based technology can effectively support character learning, although optimization for academic improvement requires time and a more comprehensive strategy. The integration of technology with appropriate pedagogical approaches provides opportunities for holistic language learning.